PRRT2 Mutations Are the Major Cause of Benign Familial Infantile Seizures - TÜRKDOĞAN, DİLŞAD (WILEY, 2012)
Mutations in PRRT2 have been described in paroxysmal kinesigenic dyskinesia (PKD) and infantile convulsions with choreoathetosis (PKD with infantile seizures), and recently also in some families with benign familial infantile seizures (BFIS) alone. We analyzed PRRT2 in 49 families and three sporadic cases with BFIS only of Italian, German, Turkish, and Japanese origin and identified the previously described mutation c.649dupC in an unstable series of nine cytosines to occur in 39 of our families and one sporadic case (77% of index cases). Furthermore, three novel mutations were found in three other families, whereas 17% of our index cases did not show PRRT2 mutations, including a large family with late-onset BFIS and febrile seizures. Our study further establishes PRRT2 as the major gene for BFIS alone. Hum Mutat 33:1439-1443, 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: synaptic vesicle; epilepsy; choreoathetosis; PRRT2; CHROMOSOME 16P12-Q12; GLUT1 MUTATIONS; CONVULSIONS; LINKAGE; EPILEPSY; CHOREOATHETOSIS; GENE; DYSKINESIA; ONSET